Christian ethics and human nature - Penelhum, Terence, 1929-2020. (Harrisburg, Trinity Press International, 2000)
"In this book (originally delivered as the John Albert Hall Lectures in Victoria, British Columbia) Terence Penelhum identifies what distinguishes the ethics of the Christian from the ethics of a secular world that commonly sees itself as having adopted Christian principles. He also tries to locate the understanding of human nature and its defects which is implied by Christian ethics. In both cases he maintains that there are continuities as well as sharp differences between the moral attitudes and the experiences of secular people and those of Christians." "However, the author's remit extends beyond that of just clarification. In comparing one set of beliefs with others, and in assessing their truth, he tries to see how the Christian view of human nature should respond to the claims of other religions. This leads to a discussion of how the Christian perspective on our nature ought to be affected by the recognition that human nature is part of Nature as a whole. It is suggested that the continuities which exist between the religions and secular moral consciousness can help us to address some of the perplexities that our own place in Nature gives rise to in the Christian mind. The book contributes to a number of significant debates, in moral theology, philosophy, and interfaith dialogue."--Jacket.
What is the Christian ethic? -- Human nature and its needs -- the Christian diagnosis -- The pluralist challenge -- Humans and the natural world.
"The 1999 Diocese of British Columbia John Albert Hall lectures at the Centre for Studies in Religion and Society in the University of Victoria."
Includes bibliographical references (pages 107-110) and indexes.
Keywords: Christian ethics